The Impact of Invisibility on the Health of Migrant Farmworkers in the Southeastern United States: A Case Study from Georgia. (1st July 2012) - Bail, Kari M.; Foster, Jennifer; Dalmida, Safiya George; Kelly, Ursula; Howett, Maeve; Ferranti, Erin P.; Wold, Judith
Abstract : Migrant farmworkers represent one of the most marginalized and underserved populations in the United States. Acculturation theory cannot be easily mapped onto the transnational experience of migrant farmworkers, who navigate multiple physical and cultural spaces yearly, and who are not recognized by the state they constitute, "the Citizen's Other" (Kerber, 2009). This paper utilizes narrative analysis of a case study to illustrate, through the relationship of the narrator to migrant farmworkers and years of participant observation by the coauthors, how isolation from family and community, as well as invisibility within institutions, affect the health and well-being of migrant farmworkers in southeastern Georgia. Invisibility of farmworkers within institutions, such as health care, the educational system, social services, domestic violence shelters, and churches contribute to illness among farmworkers. The dominant American discourse surrounding immigration policy addresses the strain immigrants put on the social systems, educational system, and the health care system. Nurses who work with farmworkers are well positioned to bring the subjective experience of farmworkers to light, especially for those engaged with socially just policies. Those who contribute to the abundant agricultural produce that feeds Americans deserve the recognition upon which social integration depends.